2021
DOI: 10.1002/er.6587
|View full text |Cite
|
Sign up to set email alerts
|

An integrated process configuration of solid oxide fuel/electrolyzer cells (SOFC‐SOEC) and solar organic Rankine cycle (ORC) for cogeneration applications

Abstract: Summary This research work presents a novel integrated structure for the cogeneration of electricity and renewable syngas. The base structure of the process is developed by solid oxide cells in which electricity is generated by the natural gas‐fueled fuel cell unit, and renewable syngas is produced by the electrolyzer cell unit. Direct integration between fuel cell and electrolyzer cell units is established for optimal use of fuel cell off‐gases. To improve system's sustainability, a solar power cycle, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The entire system can be represented mathematically by a set of algebraic equations comprised of mass balance, energy balance, and chemical species balance. 40,[49][50][51][52] The equations are written as follows:…”
Section: Mathematical Descriptionmentioning
confidence: 99%
“…The entire system can be represented mathematically by a set of algebraic equations comprised of mass balance, energy balance, and chemical species balance. 40,[49][50][51][52] The equations are written as follows:…”
Section: Mathematical Descriptionmentioning
confidence: 99%
“…Ex w is the exergy of work which is the shaft work performed by the system. Ex Q represents the exergy of thermal energy which depends on the temperature and heat of the system and can be determined as following Equation (24).…”
Section: Solution Approachmentioning
confidence: 99%
“…In addition, the hightemperature waste heat released from an SOFC stack can be used as a heat source for cogeneration applications and bottoming cycles. 23,24 Currently, there are a few researchers who focused on SOFCs fuelled by glycerol. [25][26][27] Seabae et al 25 studied the performance of an SOFC integrated with a steam reformer using different renewable fuels (ie, glycerol, ethanol, and biogas).…”
mentioning
confidence: 99%
“…The R-113 has been proven to be a good candidate for the ORP cycles. 33,34 Khalili et al 35 suggested an integrated process architecture of SOFC/SOEC combination and solar ORP unit used for cogeneration usage. The fuel cell unit's energy and exergy efficiencies could achieve 51.71% and 49.63% under design conditions.…”
Section: Introductionmentioning
confidence: 99%